Perjanjian Kerjasama Internasional dalam Konstruksi Negara Kesatuan Republik Indonesia - Welly Angela Riry; Efie Baadilla; Wilshen Leatemia; Vondaal Vidya Hattu; June M Rumalaklak (Fakultas Hukum Universitas Pattimura, 2021)
Introduction: The times have demanded international cooperative relations, including Indonesia, which is solely done to improve the welfare and prosperity of the people. International agreements are the main instrument for the implementation of international cooperative relations. Purposes of the Research: The purpose of this research is to find out and understand the position of international cooperation agreements in the construction of the Unitary State of the Republic of Indonesia.Methods of the Research: This research is a normative study using a statutory approach with the source of legal materials used primary legal materials and secondary legal materials and tertiary legal materials with qualitative analysis with deductive and inductive methods. Results of the Research: Every process of implementing and ratifying an international cooperation agreement must be carried out using formal statutory instruments so that the Indonesian state forms and issues a regulation in regulating all matters concerning international agreements, this proves the importance of establishing international cooperation and also shows that international cooperation agreements also become part of the construction of the Unitary State of the Republic of Indonesia.